2016
DOI: 10.1248/cpb.c16-00037
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Site-Selective Acylation of 10-Deacetylbaccatin III

Abstract: Organocatalytic site-selective diversification of 10-deacetylbaccatin III, a key natural product for the semisynthesis of taxol, has been achieved. Various acyl groups were selectively introduced into the C(10)-OH of 10-deacetylbaccatin III. The C(10)-OH selective acylation was also applied to acylative site-selective dimerization of 10-deacetylbaccatin III to provide the structurally defined dimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…As natural product 3 possesses a terminal glucopyranoside moiety, we envisaged that catalyst C1 would enable 4⁗-OH selective acylation, even in the presence of a total of eight free hydroxy groups. 42) Treatment of 3 with isobutyric anhydride in the presence of 10 mol% of 4-dimethylaminopyridine (DMAP) in CHCl 3 /tetrahydrofuran (THF) (9 : 1, v/v) at −60 °C gave 3⁗-O-acylate 4 as a major product with 97% site selectivity in 85% yield. This result indicated that C(3⁗)-OH had the highest intrinsic reactivity among the eight free hydroxy groups of 3 in CHCl 3 /THF (9 : 1, v/v) solution.…”
Section: Reviewmentioning
confidence: 99%
“…As natural product 3 possesses a terminal glucopyranoside moiety, we envisaged that catalyst C1 would enable 4⁗-OH selective acylation, even in the presence of a total of eight free hydroxy groups. 42) Treatment of 3 with isobutyric anhydride in the presence of 10 mol% of 4-dimethylaminopyridine (DMAP) in CHCl 3 /tetrahydrofuran (THF) (9 : 1, v/v) at −60 °C gave 3⁗-O-acylate 4 as a major product with 97% site selectivity in 85% yield. This result indicated that C(3⁗)-OH had the highest intrinsic reactivity among the eight free hydroxy groups of 3 in CHCl 3 /THF (9 : 1, v/v) solution.…”
Section: Reviewmentioning
confidence: 99%
“…148 Upon reacting 99 with anhydrides in the presence of DMAP, a slight preference for C10-acylation to yield 101 was observed (Figure 19, entry 1). However, this inherent selectivity was reinforced through the use of catalyst 73 , which afforded a 93:7 ratio of 101:100 (Figure 19, entry 2).…”
Section: Group Transfer To Hydroxyl Groupsmentioning
confidence: 99%
“…29) The amide oxygen of catalyst 6 acted as a Brøn-sted base to allow hydrogen bonding with the relatively acidic hydroxy group of the substrate, thus inducing selective acylation of the adjacent hydroxy group. We therefore considered that this catalyst may alter the selectivity of the acylation of compound 5.…”
Section: This Article Is Dedicated To Professor Satoshi ōMura In Celementioning
confidence: 99%